Utility of implantable loop recorders for diagnosing unexplained syncope in clinical practice - Entem, Felipe R. (Clin Cardiol, 2009)
BACKGROUND: Establishing a symptom–rhythm correlation in patients with unexplained syncope is complicated because of its sporadic, infrequent, and unpredictable nature. Prolonged monitoring with an implantable loop recorder (ILR) allows the recording of electrocardiogram (ECG) data from a spontaneous syncopal event. HYPOTHESIS: The aim of this study was to evaluate the usefulness of the ILR for the diagnosis of syncope of unknown origin after conventional management in clinical practice. METHODS: We reviewed the results with ILR implantation in patients with syncope of unknown origin after conventional management in the cardiology department at HU Marques de Valdecilla (Santander, Cantabria, Spain). RESULTS: One hundred and forty patients (age 64 ± 16 y; 86 male [62%]) with syncope of unknown etiology after conventional work‐up underwent prolonged monitoring with an ILR from September 1998 to February 2006; 46 patients (33%) had structural heart disease. During a mean follow‐up of 346 ± 160 d, 51 patients (36.5%) had recurrent syncope with diagnostic ECG recording. An arrhythmic cause for syncope was found in 33 of them (64.5%), with bradycardia present in 27 (53%) and tachycardia in 6 (11%). There were no sudden deaths, and 1 patient suffered a complication related to a recurrence of syncope. CONCLUSION: Long‐time experience with the ILR confirmed the utility of this device in the diagnosis of unexplained syncope in clinical practice. Most of these patients had syncope of arrhythmogenic etiology that could be successfully treated. This strategy of prolonged monitoring is safe even in patients with structural heart disease. Copyright © 2009 Wiley Periodicals, Inc.